2010
DOI: 10.1186/1758-2652-13-27
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of stigma in healthcare settings among adults living with HIV in the Islamic Republic of Iran

Abstract: BackgroundPeople living with HIV (PLHIV) sometimes experience discrimination. There is little understanding of the causes, forms and consequences of this stigma in Islamic countries. This qualitative study explored perceptions and experiences of PLHIV regarding both the quality of healthcare and the attitudes and behaviours of their healthcare providers in the Islamic Republic of Iran.MethodsIn-depth, semi-structured interviews were held with a purposively selected group of 69 PLHIV recruited from two HIV care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 46 publications
5
68
1
2
Order By: Relevance
“…For example, research documents how stigma can negatively influence the mental health of PLWHA, leading to depression, low self-esteem, and anxiety, among other effects (Li, Wang, Williams, & He, 2009; Rahmati-Najarkolaei et al, 2010; Whetten, Reif, Whetten, & Murphy-Mcmillan, 2008). Furthermore, HIV/AIDS stigma can also negatively affect physical health as it can limit access and adherence to antiretroviral treatment, which in turn accelerates disease progression and increases the risk of HIV transmission (Earnshaw, Smith, Chaudoir, Amico, & Copenhaver, 2013; Sayles, Wong, Kinsler, Martins, & Cunningham, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, research documents how stigma can negatively influence the mental health of PLWHA, leading to depression, low self-esteem, and anxiety, among other effects (Li, Wang, Williams, & He, 2009; Rahmati-Najarkolaei et al, 2010; Whetten, Reif, Whetten, & Murphy-Mcmillan, 2008). Furthermore, HIV/AIDS stigma can also negatively affect physical health as it can limit access and adherence to antiretroviral treatment, which in turn accelerates disease progression and increases the risk of HIV transmission (Earnshaw, Smith, Chaudoir, Amico, & Copenhaver, 2013; Sayles, Wong, Kinsler, Martins, & Cunningham, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Başka bir çalışmada HIV hakkında geniş bilgi sahibi olma, etiketleme ve ayrımcılık konulu eğitimlere katılmış olma, yüksek eğitim düzeyine sahip olma ve dindar olmamanın etiketleme ve ayrımcılığı azalttığı gözlenmiştir (13). İran'da sağlık çalışanları üzerinde yapılan bir çalışma sonucunda, tıbbi eğitimin etiketlemeyi azaltıcı programları içerecek şekilde güçlendirilmesi, din liderlerinden etiketleme ve ayrımcılığı azaltmaya yönelik resmi bildiriler alınması önerilmiştir (14).…”
unclassified
“…15,26 Perceived HIV-related stigma in health care can result in testing and treatment delays, avoidance of health services, and poorer quality care as a result of nondisclosure to health care providers. [30][31][32][33][34][35] In addition, perceived HIV-related stigma in health care settings can have detrimental psychological consequences, in part because perceived stigma, regardless of setting, negatively impacts psychological well-being, 14,36,37 but also because health care providers are what Goffman termed 'the wise'. 2 They are expected to have knowledge about HIV and to not discriminate against PLWH.…”
mentioning
confidence: 99%
“…Unfortunately, previous research has shown that this is not always the case. [38][39][40] Research on the impact of HIV-related stigma in health care has shown that perceived stigmatization in health care settings is related to decreased patient satisfaction, psychological distress, low self-esteem, the feeling that one is undeserving of care, and diminished motivation to stay healthy, 14,31,41 while positive interactions between health care providers and PLWH have been found to contribute to better treatment adherence and health-related quality of life. [42][43][44][45] Clearly, ensuring that PLWH feel accepted and treated equally in health care settings is imperative.…”
mentioning
confidence: 99%